Exploring Black and South Asian women’s experiences of help-seeking and engagement in perinatal mental health services in the UK - Maev Conneely; Maev Conneely; Katy C. Packer; Katy C. Packer; Sarah Bicknell; Jelena Janković; Jelena Janković; Harpreet Kaur Sihre; Rosemarie McCabe; Alex Copello; Alex Copello; Kiren Bains; et al. (Frontiers in Psychiatry, 2023)
Background and aimsIn the United Kingdom (UK), Black and South Asian women are less likely than White British women to access support from perinatal mental health services, despite experiencing similar, or higher, levels of distress. This inequality needs to be understood and remedied. The aim of this study was to answer two questions: how do Black and South Asian women experience (1) access to perinatal mental health services and (2) care received from perinatal mental health services?MethodSemi-structured interviews were conducted with Black and South Asian women (n = 37), including four women who were interviewed with an interpreter. Interviews were recorded and transcribed line-by-line. Data were analyzed using framework analysis, by an ethnically diverse multidisciplinary team of clinicians, researchers and people with lived experience of perinatal mental illness.ResultsParticipants described a complex interplay of factors that impacted on seeking, and receiving help, and benefiting from services. Four themes emerged that captured the highly varied experiences of individuals: (1) Self-identity, social expectations and different attributions of distress deter help-seeking; (2) Hidden and disorganized services impede getting support; (3) The role of curiosity, kindness and flexibility in making women feel heard, accepted and supported by clinicians; (4) A shared cultural background may support or hinder trust and rapport.ConclusionWomen described a wide range of experiences and a complex interplay of factors impacting access to, and experience of, services. Women described services as giving them strength and also leaving them disappointed and confused about where to get help. The main barriers to access were attributions related to mental distress, stigma, mistrust and lack of visibility of services, and organizational gaps in the referral process. These findings describe that many women feel heard, and supported by services, reporting that services provide a high quality of care that was inclusive of diverse experiences and understandings of mental health problems. Transparency around what PMHS are, and what support is available would improve the accessibility of PMHS.